Measuring Fluid Reasoning and Its Cultural Issues: A Review in the Indonesian Context - Hanif Akhtar (Buletin Psikologi, 2022)
Fluid reasoning (Gf) is a central component of human abilities and has been shown to be statistically indistinguishable from general cognitive ability. However, measuring fluid reasoning is not that easy since the operationalization of the construct itself is not conclusive. This situation is exacerbated if the measurements and comparisons are carried out in groups with different cultural and language abilities. The purpose of this paper is to provide a brief overview of the fluid reasoning construct as well as measurement practices that have been carried out in Indonesia. My review would mention the positioning of fluid reasoning in several intelligence theories, how researchers conceptualize fluid reasoning, how researchers measure fluid reasoning in a multicultural context, and outline critical future directions for test development. In conclusion, I emphasize the importance of using a multi-processes figural fluid reasoning test as a proxy for a culture fair intelligence test that can be used in cross-cultural assessments.